Bevölkerungsverschiebungen in Süd-Kamerun - Schramm, Joseph (ERDKUNDE, 1954)
In his reply to my paper in Erdkunde, Carlo Battisti sidetracked the problem discussed since, from the very beginning, he put the question of the Brenner frontier into the foreground and declared it an Italian postulate, whereas this point had not been my concern at all. The theme of my paper was in reality the consequences of Fascist and National-Socialist policy on the ethnical structure of South Tyrol, and the further development of the ethnical composition during the years succeeding World War II. For a number of reasons it was found necessary to devote some space to a characterization of Battisti as a person and also to the Archivio per ,1'Alto Adige. Between the two World Wars Battisti, in connexion with that publication, was actively engaged as a political propagandist who advanced the aspirations of Fascist imperialism in South Tyrol, while his concepts of the rights of ethnical minorities were contrary to the general human rights, and advocated a complete removal of the people of South Tyrol and their resettlement elsewhere. Battisti quotes in his article two sets of quite different figures relating to the size of the ethnical groups in South Tyrol, one set in the text and the other set appearing in the summary that was given in a number of languages. Since the Italian government ceased to register the ethnical affiliations of the population after the 1921 census a research worker has to base his estimate of them on the results of the various elections. The differences that exist between the figures calculated -by myself and those given by Battisti are explained by the fact that he included the military forces stationed in South Tyrol. The number of people who, after the Hitler-Mussolini agreement, opted for emigration to Germany, and have since returned, is, as quoted by Battisti, incorrect, since the majority of those that -did emigrate are prevented from returning by economic and social circumstances. Absolutely inacceptable is Battisti's claim that there is no such thing as a German-speaking population in South Tyrol. The German-speaking South Tyrolese, numbering more than 200,000, who lived in this area in 1919, and who then were matched by only 6,500 people of Italian mother tongue, have preserved their ethnical characteristics to the full as every visitor to South Tyrol will confirm. Because of that a plebiscite, which Battisti suggested as a possibility, should be confined to the German-speaking area as far south as the language boundary, and must not include the purely Italian-speaking areas of the Trentino. The language boundary of South Tyrol is clearly marked by the types of settlement, ithe economic activity and the physiognomy of the cultural landscape. This language boundary is thus the only boundary that should be applied for administrative purposes, and the only just boundary of the autonomous region within the Italian state, if the grant of autonomy to the South Tyrolese is not to he a mere farce. Historic sources confirm that the South Tyrolese are the descendants of members of the Bavarian tribe that once immigrated into (this region and are not a Germanised Latin people. On the vital paragraphs in my paper -devoted to the situation in South Tyrol between the wars, the Hitler- Mussolini agreement, and the act granting autonomy, Battisti comments in a few lines only. He also obviously overlooks all the remarks in which I appreciated the positive points in the developments in South Tyrol since 1945 for, as co-originator of the doctrine of the complete removal of the South Tyrolese, regardless of all the social and human consequences it would create, he still does not desire a compromise which would leave the country and its people their thousand year old character. It is regrettable that, for the discussion of this problem, no unbiased scholar, free from adherences to the Fascist past and open-minded about the tasks to be tackled at present and in the future, has yet presented himself.